Análise genética em grupos mistos de bugio-ruivo e bugio-preto (Alouatta guariba clamitans e Alouatta caraya) em uma zona de contato em São Vicente do Sul, Rio Grande do Sul - Dias, Thomas Dickel (2017)
There are several reports of contact zones between two species of primates of the genus Alouatta, in a few cases, forming mixed groups. The morphological variation caused by the gene flow in hybrid primates has not yet been well understood. Therefore, it is important to conduct studies to determine the presence of hybrid individuals. A contact zone described in southern Brazil has the presence of possible hybrids of A. caraya and A. g. clamitans. The objective of this study was: to verify the frequency of mixed groups of Alouatta caraya and Alouatta guariba clamitans; by mean of molecular markers (Cytb fragment) to genetically compare pure individuals with those already described with morphological characteristics for possible hybrids; with maternal and nuclear markers of hybrid individuals, determine the preferred direction of the crossing; and execute the analysis of nuclear fragments (Intron 3 of the MECP2 gene) cleaved with the restriction enzyme BspLI-CAPS by comparing the corresponding fragments for each species with the results obtained with mitochondrial DNA and phenotype analyzes.The study area is composed by riparian vegetation of the Ibicuí river and his tributaries located in the Pampa biome. Field surveys occurred monthly in 2016. Searches were conducted based on the extensive survey of previously defined forest fragments and riparian vegetation. Once located, the individuals were photographed whenever as possible and their feces collected for molecular analysis. Were identified 22 groups, 4 groups containing only individuals with A. caraya phenotype; 12 groups containing only individuals with A. g. clamitans phenotype and 6 mixed groups. Mitochondrial DNA was amplified in 22 samples and 18 samples amplified nuclear DNA, and 16 samples amplified both markers. The markers of Nuclear DNA, after being submitted to the cleavage procedure (CAPS), showed that 7 samples corresponded to A. caraya, of which 6 had the mitochondrial genotype of A. caraya. In three of five samples showed mitochondrial genotypes of A. caraya, in the other two: one show mitochondrial genotype of A. guariba and in another one the mitochondrial genotype was not accessed, in all of these five samples the nuclear genotype showed to be of A. g. clamitans. Five samples were identified as belonging to heterozygous individuals and corresponded to staining patterns identified as hybrids. Intron polymorphism analysis of the MECP2 gene in heterozygous individuals showed cleavage sites expected for both A. caraya and A. g. clamitans. Individuals with nuclear markers of A. g. clamitans and mitochondrial markers of A. caraya indicates that to some point there is viability of the hybrid individuals. This study provides new evidences of: genetically the hybridization between Alouatta caraya and A. g. clamitansthe viability of hybrid females; and the preferential fertility direction of the cross between the parent species. These results will favor new branches of study – i. e. ecological, genetic/evolutionary, behavioral, conservation, etc.